2016
DOI: 10.19126/suje.53006
|View full text |Cite
|
Sign up to set email alerts
|

Views of Advisors About Students’ Knowledge on Scientific Research Ethics an Example from Sakarya University

Abstract: In this study the views of graduate thesis advisors at Sakarya University, Institute of Educational Sciences (5 Male, 4 Female) are analysed regarding their students' knowledge on scientific research ethics (SRE). This was done via phenomenology, one of the qualitative research methods. The data were collected with structured interview questions and also additional probe questions when needed. The questions were written by the researchers after performing a comprehensive literature study. Expert opinions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Büyüköztürk (1999) found that teachers consider research competencies important, but they do not have these competencies adequately. Akgün and Güntaş (2018) stated in their study that according to the opinions of counsellors, although Ph.D. students are considered sufficient in many aspects, many competencies are not sufficient for master students. As Ph.D. students usually write a thesis at Master's level, they are expected to have more knowledge and experience.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Büyüköztürk (1999) found that teachers consider research competencies important, but they do not have these competencies adequately. Akgün and Güntaş (2018) stated in their study that according to the opinions of counsellors, although Ph.D. students are considered sufficient in many aspects, many competencies are not sufficient for master students. As Ph.D. students usually write a thesis at Master's level, they are expected to have more knowledge and experience.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…The study investigated the effect of the training programme "Journey to Literature Survey and Review" on the research competiencies of Master's degree students. Some studies in the literature investigated graduate students' research competencies (Akgün & Güntaş, 2018;Özkara, 2018;Saracaloğlu, 2008). However, these studies were generally conducted in the form of surveys and attempted to determine the level of students' research competencies or their relationships with other variables.…”
Section: Ormancı 2023mentioning
confidence: 99%
“…The students stated the negative aspects of learning by distance education as the inability to receive feedback from the instructor of the course, insufficient communication and interaction, and the inability to follow the courses regularly by the students due to low motivation. Akgün, Güleç, and Topal (2013) state that graduate distance education students have positive opinions on distance education, but they see technical infrastructure problems as an important problem. On the other hand, NCTM (2000) states that it is important to implement new strategies that will facilitate the conceptual understanding of students in mathematics education and integrate technology into the classroom and teaching.…”
Section: Introductionmentioning
confidence: 99%